Promotion of Ovarian Follicle Growth following mTOR Activation: Synergistic Effects of AKT Stimulators - Cheng, Yuan (PLoS One, 2015)
Mammalian target of rapamycin (mTOR) is a serine/threonine kinase and mTOR signaling is important in regulating cell growth and proliferation. Recent studies using oocyte- and granulosa cell-specific deletion of mTOR inhibitor genes TSC1 or TSC2 demonstrated the important role of mTOR signaling in the promotion of ovarian follicle development. We now report that treatment of ovaries from juvenile mice with an mTOR activator MHY1485 stimulated mTOR, S6K1 and rpS6 phosphorylation. Culturing ovaries for 4 days with MHY1485 increased ovarian explant weights and follicle development. In vivo studies further demonstrated that pre-incubation of these ovaries with MHY1485 for 2 days, followed by allo-grafting into kidney capsules of adult ovariectomized hosts for 5 days, led to marked increases in graft weights and promotion of follicle development. Mature oocytes derived from MHY1485-activated ovarian grafts could be successfully fertilized, leading the delivery of healthy pups. We further treated ovaries with the mTOR activator together with AKT activators (PTEN inhibitor and phosphoinositol-3-kinase stimulator) before grafting and found additive enhancement of follicle growth. Our studies demonstrate the ability of an mTOR activator in promoting follicle growth, leading to a potential strategy to stimulate preantral follicle growth in infertile patients.